Generative co-design & non-planar additive manufacture of aesthetic prostheses - Zhou, Feng (2023)
Traditionally, the prosthesis has been treated as medicalised device and primarily designed for function. The aesthetics of prostheses appeared to be a secondary concern, and even when they were considered, the appearance of prostheses often tried to mimic human limbs to hide disability. However, a new trend of aesthetic prosthesis has emerged recently which solicits attention, expresses the personal style and self-identity of the individual with limb loss or absence, and emphasises their individuality and uniqueness rather than incompleteness, which has been demonstrated to significantly impact users’ psychological well-being.